2001
DOI: 10.1088/0264-9381/18/21/302
|View full text |Cite
|
Sign up to set email alerts
|

Dirac fields and thermal effects in the de Sitter universe

Abstract: We present a study of Dirac quantum fields in a four-dimensional de Sitter spacetime. The theory is based on the requirement of precise analyticity properties of the waves and the correlation functions in the complexification of the de Sitter manifold. Holomorphic de Sitter spinorial plane waves are introduced in this way and used to construct the two-point functions, whose properties are fully characterized. The physical interpretation of the analyticity properties of Wightman's functions in terms of a KMS-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
169
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(169 citation statements)
references
References 32 publications
0
169
0
Order By: Relevance
“…A new charge conjugation has been obtained in the quantization process of the spinor field in de Sitter space constructed through ambient space notation [2,5]. It is shown that an alternative N = 2 super-symmetry algebra, mentioned but not explored in [3], can be attained by the use of the spinor fields and charge conjugation in the ambient space notation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new charge conjugation has been obtained in the quantization process of the spinor field in de Sitter space constructed through ambient space notation [2,5]. It is shown that an alternative N = 2 super-symmetry algebra, mentioned but not explored in [3], can be attained by the use of the spinor fields and charge conjugation in the ambient space notation.…”
Section: Discussionmentioning
confidence: 99%
“…The spinor wave equation in de Sitter space-time has been originally deduced by Dirac in 1935 [7], and can be obtained from the eigenvalue equation of the second order Casimir operator [4,5] (−i xγ.∂ + 2i + ν)ψ(x) = 0,…”
Section: Notationmentioning
confidence: 99%
See 1 more Smart Citation
“…Z stands for retarded, advanced, chronological and anti-chronological propagators. For example, the anti-commutator function is given by [13] …”
Section: Quantum Free Fields 21 Spinor Fieldsmentioning
confidence: 99%
“…In section 2, we briefly recall the ambient space notation and the analysis of the quantum free spinor field [11,12,13], and the quantum free vector field [11,14,16] in de Sitter space.…”
Section: Introductionmentioning
confidence: 99%